PENGARUH SOSIOLOGI HUKUM TERHADAP TERTIB BERLALU LINTAS - Ahmad Faruk (JISOS: JURNAL ILMU SOSIAL, 2023)
The density of the highway is evidence of the high volume of the number of vehicles that pass on each road. From that cause jams everywhere. Almost all regions in Indonesia experience the same thing, especially in urban areas. Along with the growth of the transportation sector, the number of accident cases has also increased. From year to year the number of accident cases continues to grow. This incident was caused by several factors, both human error, external, or others. These problems are social phenomena that need to be solved. With existing theories in sociology these symptoms can be minimized. There is a concept of legal sociology which says that law is a social control, and society as legal objects that must obey and comply with applicable law, is a practice that must be properly implemented. On the other hand, law enforcers as officers must have the courage to be honest and firm in taking action against any violations of the law in accordance with applicable laws. Law enforcers must be clean from corruption. It is intended that the authority of the law is not weakened and law enforcers and laws have the full trust of the public and no negative thinking